Spontaneous theory of mind in adults with attention-deficit/hyperactivity disorder. (June 2020) - Hayashi, Wakaho; Arai, Gosuke; Uno, Hiromitsu; Saga, Nobuyuki; Ikuse, Daisuke; Takashio, Osamu; Iwanami, Akira
Highlights: Adults with ADHD and controls were recruited. We examined implicit ToM in ADHD using the anticipatory-looking paradigm. The similar gaze pattern in both groups indicated intact implicit ToM in ADHD. Lack of gaze bias to the incongruent side indicated intact spontaneous ToM in ADHD. Shorter gaze time to the actor in ADHD may be due to inattention. Abstract: Spontaneous theory of mind (ToM) is an unconscious and automatic understanding of others' mental states. Recently, individuals with attention-deficit hyperactivity disorder (ADHD) have been shown to have social and communication difficulties, and ToM in ADHD has come under scrutiny. Although some studies have employed explicit ToM tasks to this end with contradictory results, none, to our knowledge, has investigated spontaneous ToM in individuals with ADHD. Therefore, we performed this study to examine implicit mentalizing in adults with ADHD using the anticipatory-looking paradigm designed by Senju et al. (2009) with a sample of 24 adults with ADHD and 18 neurotypical adults. The total fixation times to three areas of interest, i.e., the actor and the false-belief congruent and incongruent sides of the scene were measured. We found that neither group showed looking bias toward either the false-belief congruent or incongruent side. We interpret that this similar gaze pattern and the absence of looking bias to the false-belief incongruent side in both groups is indicative of intact implicit ToM in adults with ADHD. Adults with ADHD looked significantly less at the actor than did neurotypical individuals, possibly due to inattention and further experimental modifications should be considered.